Perceptions of Russian-Speaking Immigrants: A Case Study in Australia: Perceptions of Russian-Speaking Immigrants - Cohan Shovkovyy, Oleg (Advances in Social Sciences Research Journal, 2020)
This research was conducted in response to one of the most pressing and challenging questions on the agenda of many government offices around the world - “What can be done to better integrate and assimilate immigrants into host communities?” The qualitative study employed ethnographic methods of gathering data, where 170 Russian-speaking immigrants were observed by the insider in their natural settings, for eight months, and at different locations in Brisbane region of Australia; informal, unstructured interviews were conducted with 27 individuals. During observations, it was noticed that many immigrants had experienced one or another sort of difficulties that prevent them from smooth integration into the host society. The further analysis of data derived from immigrants narratives revealed emerging themes, which allowed identifying five factors that, perceived by immigrants as obstacles to integration: (1) employment, (2) education, (3) healthcare, (4) government assistance, and (5) discrimination. Following the logic of inductive reasoning and assumptions of grounded theory, that is seen as a research method in which the theory is developed from the data, the researcher uses research findings to build behavioral Model of Assimilation/ Integration of immigrants. Developed model not only accurately explains why immigrants resist integration but also offers the pathway to further quantification for the measurement of assimilation.